2016
DOI: 10.1002/app.43272
|View full text |Cite
|
Sign up to set email alerts
|

Acid catalyst influence on the polymerization time of polyfurfuryl alcohol and on the porosity of monolithic vitreous carbon

Abstract: This study compares the influence of different acid catalysts on the polymerization rate of polyfurfuryl alcohol (PFA) precursor and especially on the respective porosity of Monolithic Vitreous Carbon (MVC) produced from that. Five acid catalysts commonly used were compared: p-toluenesulfonic (PTLS), hydrochloric, sulfuric, nitric, and phosphoric. A fixed molar concentration of catalyst was diluted in PFA resin under room pressure and temperature. The time dependence of PFA resin polymerization was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…PFA biobased resin has been attracting massive attention in recent years because of its low cost, polar structure, and high compatibility with hydrophilic nanoparticles. Several studies on the PFA resin pot life, curing kinetics, thermal treatment can be found [11][12][13][14] and are subjects of great interest. In this sense, due to the great importance of obtaining the PFA resin with uniform quality, our group has already worked on the optimization of PFA resin synthesis to assist in the porous carbon manufacture [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…PFA biobased resin has been attracting massive attention in recent years because of its low cost, polar structure, and high compatibility with hydrophilic nanoparticles. Several studies on the PFA resin pot life, curing kinetics, thermal treatment can be found [11][12][13][14] and are subjects of great interest. In this sense, due to the great importance of obtaining the PFA resin with uniform quality, our group has already worked on the optimization of PFA resin synthesis to assist in the porous carbon manufacture [15,16].…”
Section: Introductionmentioning
confidence: 99%